2017
DOI: 10.1097/01.jaa.0000515546.68860.13
|View full text |Cite
|
Sign up to set email alerts
|

Physician assistant dual employment

Abstract: National health workforce supply and demand models help predict requirements built on individual annual productivity assumptions. Dual employment rarely is addressed, yet in 2015, about 13.5% of certified physician assistants (PAs) reported two or more clinical positions. Of PAs working two positions, 44% reported the main reason was to supplement earnings, followed by role variety. The mean number of hours worked by all certified PAs was 40.7 per week and the average number of patients was 75. Dual-employed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Smith and colleagues found that “support of and for the significant other was the most important factor in their first practice-location choice.”12 The authors concluded that recruiters should not overlook the effect of family in work location and employment decisions. Other researchers have pointed out that the first reported employment may not be as straightforward as it seems because some PAs hold dual employment 13. Also, optimal jobs may not be available at the time of graduation, but a more desirable one may appear after initial employment 14.…”
Section: Discussionmentioning
confidence: 99%
“…Smith and colleagues found that “support of and for the significant other was the most important factor in their first practice-location choice.”12 The authors concluded that recruiters should not overlook the effect of family in work location and employment decisions. Other researchers have pointed out that the first reported employment may not be as straightforward as it seems because some PAs hold dual employment 13. Also, optimal jobs may not be available at the time of graduation, but a more desirable one may appear after initial employment 14.…”
Section: Discussionmentioning
confidence: 99%
“… 19 This study of military PAs was undertaken with the intent to set the stage for a more refined examination of the dual employment role of PAs. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The questions posed to the various sources of information on PAs in the reserve components were brief and details of answers were set aside for more granular examination of roles and duality of PA careers. 20 …”
Section: Limitationsmentioning
confidence: 99%
“…The 15,771 PA respondents reported their primary job, but other NCCPA survey work has revealed that 14% may have a different secondary clinical job 14. Thus, the number of certified PAs reported in any of the specialty areas could be underreported.…”
Section: Discussionmentioning
confidence: 99%